Postoperative pulmonary rehabilitation compliance among patients with lung cancer: a cross-sectional survey - Hu, Xiangting; Sun, Fengqiu; Jiang, Lingyan (Frontiers in Oncology, 2026)
BackgroundPulmonary rehabilitation plays a pivotal role in optimizing post-operative recovery outcomes for patients with lung cancer; however, suboptimal compliance continues to pose a significant barrier to its clinical effectiveness. This study aimed to assess the current status of postoperative pulmonary rehabilitation compliance among lung cancer patients and identify the key influencing factors.MethodA cross-sectional survey was conducted with lung cancer patients who underwent surgery, using a validated scale to assess pulmonary rehabilitation compliance. Correlation analysis and multivariate linear regression analysis were conducted to evaluate the influencing factors.ResultsA total of 262 lung cancer patients were enrolled in this study (response rate 87.9%, as detailed in Supplementary File 1). The overall pulmonary rehabilitation compliance score was moderate, at 57.08 ± 9.84, with significant differences across three dimensions; notably, “active advice-seeking” had the lowest average item score (3.48 ± 1.04). Correlation analysis showed that compliance was strongly associated with age (r = -0.621, p = 0.024), educational level (r = -0.598, p = 0.017), marital status (r = 0.602, p = 0.040), place of residence (r = 0.647, p = 0.001), average monthly household income per capita (r = -0.591, p = 0.031), and lung cancer histological type (r = -0.574, p = 0.045). Multivariate linear regression analysis identified independent predictors of poorer compliance, including older age, lower educational level, unmarried/widowed/divorced status, rural residence, lower household income, and specific lung cancer classifications. The regression model demonstrated good fit (R²=0.591, F = 28.558, p < 0.001).ConclusionPostoperative pulmonary rehabilitation adherence among lung cancer patients still has considerable room for improvement, highlighting the need for multi-dimensional, targeted strategies to enhance patient compliance.